SPIRIT OF NOAH : MEMAKNAI ULANG SEMANGAT KENABIAN DALAM ALKITAB MELALUI KARYA SENI RUPA - Sitompul, Theresia Agustina (Institut Seni Indoensia Surakarta, 2018)
In the legend of Noah's Ark, God punished one whole generation of Noah who were wicked and defying God by sending a natural disaster in the form of the Great Flood, destroying the nature. Noah was commanded to build an ark (medium) to save himself, his family, and his followers, also all kind of animals in pairs; to save a generation of life that later will create a new civilization and culture in a new area or location. The legend of Noah's Ark can be found in almost every holy book of divine religions where the story conveys the message of a life-cycle and how we learn about the meaning of life.Associating the story with our current lives, Noah's Ark has two concepts of interpretation; in the context of salvation and at the same time as a mediation space of the birth of a new culture. How human save themselves from their worldly problems, and at the same time a mediation space, a shifting space from the old culture into the new culture. These two concepts of Noah's Ark are the background and the base this creation for the writer. Keywords : Spirit of Noah, graphic art, hermeneutika.